The Relationship between Sleep Quality and Blood Pressure in Students of the Faculty of Medicine, Universitas Prima Indonesia - Dinda Rahmah Aulia; Nadia Resonia Goviana; Rahmad Isnanta (HM Publisher, 2023)
Poor sleep quality is one of the risk factors for high blood pressure or hypertension in adults. Disorders of the cardiovascular system are believed to be one of the effects of poor sleep quality. This study aims to determine the relationship between sleep quality and cardiovascular performance of students at the Faculty of Medicine, Universitas Prima Indonesia, as assessed by systolic and diastolic blood pressure. This study is an observational study with a cross-sectional approach. A total of 75 subjects participated in this study. Sleep quality was assessed by PSQI, and blood pressure was assessed by an aneroid tensimeter. This study shows that sleep quality is related to blood pressure. Poor sleep quality is associated with increased blood pressure, p<0.05. Sleep quality is related to blood pressure in students of the Faculty of Medicine, Universitas Prima Indonesia.